REPUTASI UNDERWRITER DAN UNDERPRICING TERHADAP KINERJA KEUANGAN SAAT INITIAL PUBLIC OFFERING (IPO) - Suci Anggraini; Aminar Sutra Dewi (Lembaga Penelitian Dan Pengabdian Masyarakat (LPPM) Sekolah Tinggi Ilmu Ekonomi (STIE) Pontianak, 2023)
This study aims to know the effect of underwriter reputation and underpricing on the financial performance of companies conducted an Initial Public Offering (IPO) listed on the Indonesia Stock Exchange for the 2017-2021 period. The type of research is quantitative and used secondary data obtained from the Indonesian Stock Exchange website. The population are all companies that have conducted an Initial Public Offering (IPO) that are listed on the Indonesia Stock Exchange during the 2017-2021 observation period. The total population of this study is 252 companies and samples were 60 companies. Sampling in this study using a purposive sampling technique. Methods of data analysis using Ordinary Least Square, with a multiple regression model approach and statistical t-test. Data analysis used eviews 12. The results of the study show that underwriting history has a negative and no significant. Underpricing has a significant positive.